A generalized method for detecting abnormal returns and changes in systematic risk - Ken B. Cyree; Ramon P. DeGennaro (Federal Reserve Bank of Atlanta, 2001)
The authors generalize traditional event-study techniques to allow for event-induced parameter shifts, shifting variances, and firm-specific event periods. Their method, which nests traditional methods, also permits systematic risk to change gradually during the event period and exit the period at higher or lower levels. The authors use their approach to study 132 banks that acquired other institutions between 1989 and 1995. The authors find a significant change in the systematic risk of the acquiring firms, significant ARCH effects, and an event period that ends before the date of the announcement. None of these results is detectable using conventional methods. These results imply that (1) event studies that cannot account for information leakage may be biased, and (2) changes in systematic risk can occur in the absence of abnormal returns, and (3) regulators, investors and bank managers must evaluate each acquisition on its own merits; reliance on averages can mask important distinctions across acquisitions.
Keywords: 330; Bank mergers; Econometric models; Risk